Kinematical comparison of A & H type start stances in speed skating - Ryu, S.; Jun, M.-K.; Park, S.; Yoon, S. (Korean Journal of Sport Biomechanics, 2025)
Objective: This study aims to examine the kinematic differences between A-type and Htype start stances in speed skating. Method: Nine collegiate speed skaters (Age: 22.4 ± 1.7 years, Height: 174.0 ± 5.4 cm, Body Weight: 69.3 ± 5.7 kg) performed three trials of each start stance (A-type, H-type). Start motions were recorded using a 9-camera infrared motion capture system (100 Hz) with 48 reflective markers attached to major body segments. Kinematic variables, including the center of mass (COM) displacement, COM velocity, Base of support (BOS)-COM horizontal distance, push-off angle, and lower-limb joint range of motion (ROM), were analyzed across nine event-based phases. Results: The H-type stance showed a shorter execution time in the early phases (P1 and P3), whereas the A-type stance demonstrated greater anterior COM displacement and higher mean COM velocity in most phases (p<.05). The BOS-COM horizontal distance was significantly larger in the H-type stance (p<.05), indicating reduced initial stability. Push-off angles in the left (P4) and right (P6) push-off phases were greater in the H-type stance (p<.05). Additionally, the A-type stance exhibited greater hip and knee joint ROM during early push-off phases (p<.05). Conclusion: These findings indicate that the A-type stance is advantageous for achieving greater forward momentum and acceleration through larger joint utilization, whereas the H-type stance is effective for rapid initial reactions and efficient force transmission during push-off. Therefore, the selection of start stance may be optimized by considering individual skaters' physical characteristics and performance requirements.